LEARN, PLAY, AND EXPLORE: DISCOVERING EDUTECHMENT AT TAMAN PINTAR YOGYAKARTA - Sazliana Idmi Martuji; Joko Pamungkas (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The changing characteristics of children’s learning in the digital era have created a need for learning environments that are more interactive, visual, and experience-based. Conventional learning is increasingly considered less effective in maintaining children’s engagement due to limited opportunities for exploration and direct interaction during the learning process. In response to this condition, the concept of edutechment has emerged as an approach that integrates educational and entertainment elements to create more enjoyable and meaningful learning experiences. This study aims to analyze the implementation of edutechment at Taman Pintar Yogyakarta as a nonformal educational tourism space. This study employed a qualitative approach using a descriptive observational research design. Data were collected through direct observation, semi-structured interviews, documentation, and field notes involving child visitors, guides, and employees of Taman Pintar. The data were analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed that Taman Pintar Yogyakarta has implemented the concept of edutechment through the integration of technology, multimedia, simulations, and educational play activities within various interactive attractions. Children were actively involved in exploration, experimentation, and direct interaction with learning media, creating more concrete and enjoyable learning experiences. However, the study also found that some children tended to focus more on entertainment aspects than on understanding educational concepts. Therefore, stronger facilitation and reflective learning strategies are needed to optimize the implementation of edutechment.